Papua New Guinea Kimbe Biala Transmission Line Pacific project brief. (Metro Manila, Philippines Asian Development Bank, 2017)
The 150 kilometer high voltage transmission line linking towns in Papua New Guinea will bring electricity from renewable energy sources to households, schools, and medical clinics.
Keywords: Economic development projects; Hydroelectric power plants -- Finance; Energy consumption -- Papua New Guinea; Electronic books